Analisis Impelmentasi Layanan Bimbingan Belajar Untuk Mengatasi Ketidakmampuan Dalam Membaca Pada Siswa Kelas VII SMP Negeri 8 Kupang - Lotu, Berenika; Nalle, Andriani Paulin; Masi, Lolang Maria; Abel, Rizky Mayesita Aryance (JURNAL BIMBINGAN KONSELING FLOBAMORA, 2024)
The process of implementing tutoring to overcome students' inability to read includes concrete steps which are classified into three stages, namely before guidance which includes case identification, problem identification and diagnosis. This stage is carried out to understand the root of students' problems in reading. During guidance, which includes a prognosis stage or a stage where alternatives are determined in overcoming the problem of a student's inability to read, where alternative problems are determined by considering the student's condition and needs. After being given guidance which includes the evaluation and follow-up stages, this stage is carried out to monitor students' progress in reading after being given tutoring services. This research aims to describe the implementation of tutoring to overcome reading disabilities in class VII students at SMP Negeri 8 Kupang. The approach and type of research used in this research is qualitative, with a case study type of research. The data collection techniques used in this research are interviews, observation and documentation. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. The data validation techniques that researchers use are source triangulation and technical triangulation. The research results show that the implementation of tutoring to overcome reading disabilities in class VII students at SMP Negeri 8 Kupang is classified into 3, namely before tutoring, during tutoring and after being given tutoring. At the stage before guidance, the guidance and counseling teacher carefully identifies cases and problems, including identifying specific difficulties experienced by students in reading, such as difficulty reading haltingly and difficulty distinguishing the same letters. Next, at the tutoring stage, the guidance counselor determines a prognosis and offers alternatives in overcoming problems. What the guidance counselor does at this stage is that the guidance counselor provides tutoring services using the individual tutoring method. In this tutoring, the guidance and counseling teacher teaches students about learning to read with vocabulary, learning to read with spelling and learning to recognize letters. Finally, at the stage after guidance, evaluation and follow-up, the guidance and counseling teacher monitors students' progress in reading using reading journals and student reading monitoring sheets at home. Based on the research results, it can be concluded that a structured and systematic approach is very important in helping students overcome their learning difficulties. By dividing the tutoring process into three stages, namely before, during, and after tutoring, counselors can effectively identify problems, determine a prognosis, and evaluate student progress.